The potential of location-based gamification apps for promoting Sofia as a tourist destination - Mileva, Sonia; Assenova, Mariana; Petrov, Emil; Gyaurova, Veneta (Turyzm/Tourism, 2021)
The main aim of the research is to identify the potential of location-based gamification apps for promoting tourist destinations. The specific goal is to investigate and evaluate the existing gamified apps for Sofia and reveal their potential as a marketing tool for enhancing the capital as a tourist destination. The study is based on a literature review on the topic and desk research of the available location-based gamification apps for promoting Sofia as a tourist destination thus allowing a comparative analysis of the main attributes of the gamified apps to be made. The qualitative research technique of using key informants is also applied, providing an expert source of information and a deeper insight into current and potential practices in the research area and their effectiveness. The results indicate that this has the greatest potential for further engagement of users and the co-creation of products and services as well as for raising awareness of the destination. The main limitations are related to the fact that they are a relatively new and little-known marketing tool in the field of tourism, and this predetermines a lack of sufficient knowledge and experience for their use for promotional purposes.